Exploring the likelihood of Black women self-actualizing: the struggle to recover from racial trauma - Blanford, Winsora (2012)
This paper examines how Black women who have experiened trauma make meaning of lived experiences. The informants' autobiographies provide data for a team approach to psychological phenomenology, a psychological autopsy. The inner lives are traced from pre trauma to self-actualization. Anger, shame, and fear, as well as, love, belonging, running and relationships with other women are investigated